Diverse Intracellular Inclusion Types Within Magnetotactic Bacteria: Implications for Biogeochemical Cycling in Aquatic Environments. Issue 7 (12th July 2021) - Li, Jinhua; Liu, Peiyu; Tamaxia, Alima; Zhang, Heng; Liu, Yan; Wang, Jian; Menguy, Nicolas; Zhao, Xiang; Roberts, Andrew P.; Pan, Yongxin
Abstract: Magnetotactic bacteria (MTB) are a group of prokaryotes that generally live dominantly at or just below the oxic‐anoxic transition zone (OATZ) in diverse aquatic environments. They biomineralize intracellular magnetic nanocrystals of magnetite (Fe3 O4 ) or/and greigite (Fe3 S4 ) each enveloped by a bilayer membrane, called a magnetosome, and often organized into a chain or chains. Here, we identify a new magnetotactic spirillum strain (tentatively named WYHS‐1) from freshwater sediments of Weiyang Lake, Xi'an, northwestern China, using coupled fluorescence and transmission electron microscopy at the single‐cell level. Phylogenetic analysis of the 16S rRNA gene sequence indicates that strain WYHS‐1 is affiliated with the Azospirillum genus within the Alphaproteobacteria class of the Proteobacteria phylum. Transmission electron microscopy combined with synchrotron‐based scanning transmission X‐ray microscopy analyses reveal that strain WYHS‐1 produces nearly isotropic magnetite‐type crystals, with average lengths and widths of 34.5 ± 6.7 nm and 32.8 ± 6.5 nm, respectively. WYHS‐1 cells also contain at least three other types of intracellular, submicron inclusions: Sulfur (S 0 ) globules, Ca/Mg‐rich polyphosphate granules, and organic‐deficient vacuoles. Unlike magnetic particles, which occur within all WYHS‐1 cells, the latter three inclusion types are not always present, which indicates that they may be temporary intracellular structures that store or transport chemicals. Together with genomic and physicochemical knowledge for available bacteria, we propose a conceptual model in which MTB drive biogeochemical elemental cycling within aquatic OATZ environments and contribute to the distribution and burial of biominerals in sediments. Plain Language Summary: Inclusions are common in all cells. Cellular inclusions within microbes are used for nutrient storage or as microcompartments, or even as organelles involved in bacterial movement. Magnetic particles that form within organelles called magnetosomes are among the most remarkable inclusions because the enclosed biomineralized magnetic particles are used by aquatic magnetotactic bacteria (MTB) to navigate in Earth's magnetic field. We report here a novel magnetotactic spirillum strain WYHS‐1 that belongs phylogenetically to the Azospirillum genus and produces magnetite particles. It can also form at least three other types of intracellular, submicron inclusions: sulfur globules, Ca/Mg‐rich polyphosphate granules, and organic‐deficient vacuoles. Together with genomic and physicochemical knowledge for available bacteria, we propose a conceptual model in which MTB drive biogeochemical elemental cycling within aquatic oxic‐anoxic transition zone environments by coupling geomagnetic‐guided up‐down shuttling with redox‐related metabolic dynamics. Key Points: A novel magnetotactic spirillum WYHS‐1 was studied systematically with fluorescence‐coupled transmission electron microscopy (FISH‐TEM), transmission electron microscopy (TEM), and scanning transmission X‐ray microscope (STXM) methods WYHS‐1 produces intracellular magnetite crystals, sulfur (S 0 ) globules, Ca/Mg‐rich polyphosphate granules, and vacuoles We propose a conceptual model that magnetotactic bacteria (MTB) drive biogeochemical elemental cycling within aquatic oxic‐anoxic transition zone (OATZ) environments